Predictors of ManuScript Rejection sYndrome (MiSeRY): a cohort study. Issue 11 (8th December 2019) - Han, Hui‐Chen; Koshy, Anoop Ninan; Lin, Tina; Yudi, Matias; Clark, David; Teh, Andrew W; Farouque, Omar
Abstract: Objectives: To assess whether specific factors predict the development of ManuScript Rejection sYndrome (MiSeRY) in academic physicians. Design: Prospective pilot study; participants self‐administered a questionnaire about full manuscript submissions (as first or senior author) rejected at least once during the past 5 years. Setting: Single centre (tertiary institution). Participants: Eight academic physician‐authors. Main outcome measures: Duration of grief. MiSeRY was pre‐specified as prolonged grief (grief duration longer than the population median). Results: Eight participants provided data on 32 manuscripts with a total of 93 rejections (median, two rejections per manuscript; interquartile range [IQR], 1–3 rejections per manuscript). Median age at rejection was 37 years (IQR, 33–45 years); 86% of 80 rejections involved male authors (86%), 56 of the authors providing data about these rejections were first authors (60%). The median journal impact factor was 5.9 (IQR, 5.2–17). In 48 cases of rejection (52%), pre‐submission expectations of success had been high, and in 54 cases (58%) the manuscripts had been sent for external review. Median grief duration was 3 hours (IQR, 1–24 h). Multivariate analysis indicated that higher pre‐submission expectation (adjusted odds ratio [aOR], 5.0; 95% CI, 1.5–18), first author status (aOR, 9.5; 95% CI, 1.1–77), and external review (aOR, 19.0; 95% CI 2.9–126) were independent predictors of MiSeRY. Conclusions: To help put authors out of their MiSeRY, journal editors could be more selective in the manuscripts they send for external review. Tempering pre‐submission expectations and mastering the Coping and reLaxing Mechanisms (CaLM) of senior colleagues are important considerations for junior researchers.